Additive manufacturing method of yttrium oxide ceramic core
By surface coating and activation of spherical yttrium oxide powder, the problem of powder absorbing adhesive in adhesive spray printing is solved, and the rapid, low-cost and lightweight manufacturing of yttrium oxide ceramic core is achieved, and the finished product is improved rate and structural integrity.
Patent Information
- Application Number
- CN202411655801.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
When preparing yttrium oxide core by spray printing, nano-granulated spherical yttrium oxide powder easily absorbs the binder, resulting in poor part forming effect and affecting the shape and surface accuracy of the ceramic core.
By surface coating and activation of spherical yttrium oxide powder, di(dioctyl pyrophosphate) vinyl titanate is used as the coating agent and fatty alcohol polyoxyethylene ether as the surfactant, the modified powder is bonded to the bond after the modification The adhesive is not absorbed during the agent spray printing, which improves the forming accuracy.
It realizes rapid, low-cost and lightweight manufacturing of yttrium oxide ceramic cores, improves yield and structural integrity, and meets the requirements of industrial production.
Smart Images

Figure CN119490352A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic cores for active metal precision casting, and in particular relates to an additive manufacturing method for yttria ceramic cores. Background Art
[0002] Titanium alloys are widely used in aerospace, biomedicine, electronic devices and many other fields due to their high specific strength, good corrosion resistance, excellent high temperature resistance and stable biocompatibility. With the growing demand for "high, precise and advanced" titanium alloy casting in cutting-edge fields, lightweight complex parts have become the focus of attention of all countries. Yttrium oxide has good high temperature stability, low thermal expansion coefficient, and does not react with titanium alloy at high temperature. It is an excellent material for preparing cores for titanium alloy casting.
[0003] The preparation of complex ceramic cores is the key to titanium alloy precision casting. The traditional preparation of yttrium oxide cores mainly adopts the lost wax molding process. However, with the continuous improvement of industrial requirements, the traditional lost wax molding process has the following obvious disadvantages:
[0004] 1) Lost wax molding usually requires the preparation of wax molds. For titanium alloy castings with complex structures, there are difficulties in mold design, long manufacturing cycle, high cost, high processing difficulty and low yield rate;
[0005] 2) The lost wax molding method requires the ceramic slurry to be coated over and over again, and the prepared ceramic cores are all solid. If a larger ceramic core is prepared, the weight is too large, which does not meet the lightweight requirements and causes great difficulties for subsequent core removal.
[0006] With the rapid development of additive manufacturing technology, ceramic cores for titanium alloy precision casting have a simpler and faster preparation method. Binder jet printing technology can be mass-produced, low-cost, can be prepared in an atmospheric environment, and will not introduce internal stress. It has significant advantages in the preparation of ceramic cores. Binder jet printing can prepare complex ceramic cores simply and quickly, but complex parts can only be sintered by pressureless sintering. Yttrium oxide has a high melting point of more than 2400 degrees, and sintering is too difficult. Therefore, nano-granulated powder with low sintering driving force and strong diffusion ability is selected as the raw material for binder jet printing. However, direct printing of granulated spherical yttrium oxide powder will absorb the binder, resulting in poor part forming effect, seriously affecting the shape and surface accuracy of the ceramic core. Summary of the invention
[0007] In view of the problem of binder absorption in the current binder jet printing technology for preparing yttrium oxide cores, the present invention provides an additive manufacturing method for yttrium oxide ceramic cores, which can achieve rapid, low-cost and lightweight manufacturing of yttrium oxide complex ceramic cores for titanium alloy precision casting, and ensure structural completion and high yield rate to meet the requirements of industrial production.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] The present invention provides an additive manufacturing method for an yttria ceramic core, comprising the following steps:
[0010] Step 1, performing surface coating treatment on spherical yttrium oxide powder;
[0011] Step 2, performing surface activation treatment on the spherical yttrium oxide powder treated in step 1;
[0012] Step 3, washing, drying and crushing the spherical yttrium oxide powder processed in step 2;
[0013] Step 4, mixing the spherical powder processed in step 3 with the irregular yttrium oxide powder according to particle size grading;
[0014] Step 5, performing bonding spray printing and molding on the powder mixed in step 4;
[0015] Step 6, curing the yttrium oxide ceramic core blank printed in step 5;
[0016] Step 7, performing a powder removal treatment on the yttrium oxide ceramic core after the curing treatment in step 6;
[0017] Step 8, high-temperature sintering the yttrium oxide ceramic core after the powder cleaning in step 7 to obtain the yttrium oxide ceramic core.
[0018] Further, the spherical yttrium oxide powder described in step 1 refers to a spherical yttrium oxide powder with a particle size of 10 μm obtained by nano-granulation of yttrium oxide; the reason for selecting the nano-granulated spherical powder is that the spherical yttrium oxide obtained by nano-granulation has a smaller particle size and can fill the gap between the irregular powders with larger particle sizes during the subsequent grading optimization, thereby increasing the packing density of the powder, and can improve the fluidity of the powder during the printing process to obtain a powder bed with a higher density, and in the subsequent high-temperature sintering, the nano-yttrium oxide is more likely to undergo mass transfer, which can promote the high-temperature sintering of the yttrium oxide ceramic core, improve the ceramic strength, and reduce the sintering temperature;
[0019] The specific process of surface coating the spherical yttrium oxide powder in step 1 is as follows: adding granulated spherical yttrium oxide powder with a particle size of 10 μm into a ball mill, adding 1 to 3 g of di(dioctyl pyrophosphate)vinyl titanate as a surface coating agent for every 100 g of spherical yttrium oxide powder, and using xylene as an organic solvent; adding alumina ball milling beads of the same mass as the powder as abrasives, and adding ball milling beads with diameters of 10 mm, 5 mm, and 2 mm in a ratio of 1:1:1; the horizontal rotation speed of high-energy ball milling mixing is 800 r / min, and the high-energy ball milling mixing time is 4 to 12 h; the purpose of adding ball milling beads of different diameters is to allow the granulated spherical yttrium oxide powder to be fully mixed with di(dioctyl pyrophosphate)vinyl titanate in xylene to achieve the purpose of powder surface coating.
[0020] Furthermore, the specific process of surface activation treatment of the spherical yttrium oxide powder treated in step 1 described in step 2 is: adding a non-ionic surfactant to the spherical yttrium oxide powder after treatment in step 1, adding 1 to 3 g of fatty alcohol polyoxyethylene ether as a surfactant for every 100 g of spherical yttrium oxide powder; continuing high-energy ball milling, the horizontal rotation speed of high-energy ball milling mixing is 400 r / min, and the high-energy ball milling mixing time is 8 to 16 hours.
[0021] During the binder jet printing process, the nano-granulated spherical yttrium oxide powder will absorb the binder printed in the selected area, and the binder cannot be present between the yttrium oxide powders, which greatly affects the formability of the ceramic core; di(dioctyl pyrophosphate)vinyl titanate is used as the surface coating agent of the nano-granulated spherical yttrium oxide powder because di(dioctyl pyrophosphate)vinyl titanate is a chelating titanate coupling agent with strong hydrophobicity and hydrolysis stability; after coating the granulated spherical yttrium oxide powder, the absorption of the binder by the granulated spherical yttrium oxide powder can be well avoided. The non-ionic surfactant fatty alcohol polyoxyethylene ether is used to treat the surface activity of the coated granulated spherical yttrium oxide powder to improve the surface activity of the granulated spherical yttrium oxide and the wettability with the water-based binder; after the two-step modification of surface coating and surface activation treatment, the granulated spherical yttrium oxide powder that does not absorb the water-based binder and has better wettability with the water-based binder can be successfully obtained.
[0022] Furthermore, in the step 3, the spherical yttrium oxide powder treated in step 2 is cleaned by ultrasonic vibration cleaning, the ultrasonic frequency is 100kHz, the cleaning liquid is a 75% alcohol solution, and the cleaning time is 10 to 20 minutes, the purpose is to clean out the xylene and organic matter in the powder; the temperature for drying the cleaned granulated spherical yttrium oxide powder is 80 to 100°C, and the drying time is 2 to 4 minutes, to ensure that the organic matter in the granulated spherical yttrium oxide powder is completely volatilized with the alcohol; the speed of crushing the dried granulated spherical yttrium oxide powder is 500 to 1500r / min, and the crushing time is 10 to 20s, in order to separate the partially agglomerated powder, and finally the powder is sieved through a 1000-mesh sieve to prepare for subsequent bonding and binder jet printing.
[0023] Further, the 30 μm irregular powder in step 4 refers to an irregularly shaped yttrium oxide powder with a particle size of about 30 μm after direct chemical formation and screening, and the irregular yttrium oxide powder has a low cost. The specific process of particle size grading mixing is: the modified spherical yttrium oxide powder with a particle size of 10 μm and the irregular yttrium oxide powder with a particle size of 30 μm are assembled and placed in a ball mill according to different mass ratios of 1 to 4: 9 to 6. Then, ball milling beads with a diameter of 10 mm and a ratio of 5 mm of 1:1 are added to the ball milling jar. The horizontal speed of the ball milling mixing is 200 r / min, the vertical speed is 30 r / min, and the ball milling mixing time is 4 to 6 hours, aiming to fully mix the two yttrium oxide powders of different particle sizes. The irregular powder reduces the cost of the yttrium oxide ceramic core in the preparation process, the spherical powder improves the fluidity of the powder during the printing process, and the spherical powder with a smaller particle size can fill the gaps in the irregular powder, thereby improving the density of the yttrium oxide ceramic core.
[0024] Furthermore, the binder jetting 3D printing equipment in step 5 mainly includes a system operating computer, a powder feeding cylinder, a forming cylinder, a roller, a nozzle and a motor control system. The system operating computer is used to import the target model of the binder jet printing, the model is in STL format, and to set the parameters measured during the binder jet printing process, such as the printing layer thickness, the binder saturation, the roller rotation direction and speed; the powder feeding cylinder is located on the right side of the forming cylinder, the yttrium oxide powder to be printed is pre-loaded in the powder feeding cylinder, and then the yttrium oxide powder is pushed from right to left to the forming cylinder by the roller, and then the nozzle prints the binder of the preset graphic shape in the system operation on the forming cylinder, and the powder feeding cylinder rises by a layer thickness. The height of the forming cylinder is lowered by a layer thickness, and then the roller pushes the powder, and the nozzle prints, and the cycle repeats. In the present invention, the layer thickness is set to 80-120 μm; the speed and rotation direction of the roller are controlled by a motor, and the roller is located above the forming cylinder and the powder feeding cylinder to complete the powder feeding from right to left. In the present invention, the roller rotates counterclockwise at a speed of 60 r / min; the nozzle is a Ricoh G6 nozzle suitable for printing water-based binders. The nozzle is controlled by a control panel and a motor, and is located above the forming cylinder. After the roller feeds the powder, the part pattern preset by the operating system is printed on the powder bed. The saturation of the binder printed by the nozzle of the present invention is 54-80%, and the number of prints is 2 passes.
[0025] The specific steps of binder jet printing to prepare yttria ceramic cores are:
[0026] ① Turn on the system operating computer, turn on the power of the binder jet printer, and import the target part STL file into the computer;
[0027] ② Pour the mixed yttrium oxide powder into the powder feeding cylinder and the water-based binder into the ink cartridge;
[0028] ③ Start the additive manufacturing software, set the roller to rotate counterclockwise, the rotation speed is 60r / min, the printing layer thickness is 80-120μm, the nozzle printing binder saturation is 54-80%, and the printing number is 2pass; the mixed yttrium oxide powder is printed by binder jetting, and the yttrium oxide ceramic core blank is buried in the powder bed;
[0029] ④ Take out the entire printed powder bed from the forming cylinder and put it into the oven;
[0030] ⑤ Exit the additive manufacturing system software, turn off the computer power switch, and turn off the binder jet printer switch.
[0031] Furthermore, the curing after printing in step 6 refers to: placing the powder bed after printing into an oven, setting the temperature to 110-130°C, and keeping the temperature for 2-4 hours, so that the aqueous binder is fully cross-linked and cured within a suitable temperature range, and the yttrium oxide powder is firmly connected together under the action of the binder to form an yttrium oxide ceramic core blank.
[0032] Furthermore, in step 7, the powder cleaning is to remove the powder on the surface of the solidified yttrium oxide ceramic core blank by using a brush, an air gun, etc. after the yttrium oxide powder bed is solidified. These powders are not bonded by the binder and can be reused after cleaning.
[0033] Furthermore, the specific process of high-temperature sintering in step 8 is as follows: the yttrium oxide ceramic core blank after powder cleaning is placed in a mullite crucible, placed in a high-temperature box furnace for high-temperature sintering, heated to 1200°C at a heating rate of 10°C / min and kept warm for 1h, then heated to 1500°C / 1600°C / 1700°C at a heating rate of 2°C / min and kept warm for 2h, then cooled to 1200°C at a cooling rate of 2°C / min, and cooled to 300°C at a cooling rate of 10°C / min; the binder is fully burned and volatilized at high temperature to avoid residue, and the yttrium oxide powder is also sintered and dense at high temperature, and finally an yttrium oxide ceramic core that can be used for titanium alloy casting is formed.
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] 1. Additive manufacturing technology can be used to quickly and inexpensively prepare lightweight and complex yttria ceramic cores, greatly shortening the core preparation cycle and cost, and better meeting the requirements of rapid iteration of industrial production.
[0036] 2. Compared with other ceramic core additive manufacturing technologies, binder jetting technology does not require a heat source, has high production efficiency, can be printed in an atmospheric environment, has low cost, and can be mass-produced.
[0037] 3. Use nano-granulated spherical yttrium oxide powder with a particle size of 10μm and irregular yttrium oxide powder with a particle size of 30μm for grading, and use the spherical powder with a smaller particle size to fill the gap between the irregular powders. During the sintering process, the yttrium oxide with a larger particle size basically does not change in shape, which plays a role in dimensional accuracy. The nano-granulated yttrium oxide has low sintering drive and strong diffusion ability, which reduces the difficulty of sintering.
[0038] 4. The "coating-activation" surface modification technology is innovatively applied to binder jet printing of yttrium oxide ceramics. After being treated in this way, the nano-granulated powder can also be formed by binder jet printing, which not only retains the advantages of nano-powder in the subsequent sintering stage, but also broadens the application of granulated powder in binder jet printing. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a microstructure diagram of granulated spherical yttrium oxide powder and a schematic diagram of its wettability with aqueous binder before and after modification.
[0040] Figure 2 Graph 1 shows the porosity of the yttria ceramic preforms of different embodiments.
[0041] Figure 3 The bending strength of the sintered samples of yttria ceramics in different embodiments.
[0042] Figure 4 The hollow yttria ceramic core is prepared according to Example 2.
[0043] Figure 5 Schematic diagram of the granulated yttrium oxide powder wetting the binder before and after modification.
[0044] Figure 6 The pH curve of yttrium oxide aqueous solution after adding different contents of di(dioctyl pyrophosphate) vinyl titanate
[0045] Figure 7 The wetting angle between yttrium oxide and water-based binder after adding fatty alcohol polyoxyethylene ether DETAILED DESCRIPTION
[0046] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.
[0047] Example 1
[0048] This embodiment is an additive manufacturing method for an yttria ceramic core, and the specific process thereof includes the following steps:
[0049] Step 1, surface coating the spherical yttrium oxide powder: add granulated spherical yttrium oxide powder with a particle size of 10 μm into a ball mill, add 1 g of di(dioctyl pyrophosphate)vinyl titanate as a surface coating agent for every 100 g of spherical yttrium oxide powder, and use xylene as an organic solvent; add alumina ball milling beads of the same mass as the powder as abrasives, and the diameters of the ball milling beads added are 10 mm, 5 mm, and 2 mm in a ratio of 1:1:1; the horizontal rotation speed of high-energy ball milling mixing is 800 r / min, and the high-energy ball milling mixing time is 4 hours.
[0050] Step 2, performing surface activation treatment on the spherical yttrium oxide powder treated in step 1: adding a nonionic surfactant to the spherical yttrium oxide powder treated in step 1, adding 1g of fatty alcohol polyoxyethylene ether as a surfactant for every 100g of spherical yttrium oxide powder; continuing high-energy ball milling, the horizontal rotation speed of high-energy ball milling mixing is 400r / min, and the high-energy ball milling mixing time is 8h.
[0051] Step 3, cleaning, drying and crushing the spherical yttrium oxide powder treated in step 2: placing the spherical yttrium oxide powder treated by surface activation in step 2 into an alcohol solution with a volume percentage of 75% for ultrasonic cleaning for 10 minutes, with an ultrasonic frequency of 100kHz, and drying the spherical yttrium oxide after cleaning at a temperature of 80°C for 2 hours; crushing the dried spherical yttrium oxide powder with a pulverizer at a crushing speed of 500r / min and a crushing time of 10s, and finally sieving the powder through a 1000-mesh sieve.
[0052] Step 4, mixing the spherical powder treated in step 3 with the irregular yttrium oxide powder according to particle size grading: ball-milling the modified spherical yttrium oxide powder with a particle size of 10 μm and the irregular yttrium oxide powder with a particle size of 30 μm in a mass ratio of 1:9, and adding ball milling beads with a diameter of 10 mm and 5 mm in a ratio of 1:1; the horizontal speed of the ball milling is 200 r / min, the vertical speed is 30 r / min, and the ball milling time is 4 hours.
[0053] Step 5, the powder mixed in step 4 is subjected to binder jet printing: the required yttrium oxide ceramic core pattern is drawn by 3D modeling software, and printed by a binder jet device; the specific printing parameters are as follows: the printing layer thickness is 80 μm, the printing binder saturation is 54%, the printing number is 2 passes, the roller rotates counterclockwise, and the rotation speed is 60 r / min.
[0054] Step 6, solidify the yttrium oxide powder bed printed in step 5: put the printed powder bed into an oven, set the temperature to 110°C, and keep it warm for 2 hours to fully solidify the binder to form a firm yttrium oxide ceramic core blank.
[0055] Step 7, performing a powder cleaning treatment on the yttrium oxide ceramic core after the solidification treatment in step 6: removing excess yttrium oxide powder from the surface and the inside of the solidified yttrium oxide ceramic preform by brushing.
[0056] Step 8, high-temperature sintering the yttrium oxide ceramic core after the powder cleaning in step 7 to obtain the yttrium oxide ceramic core: the yttrium oxide ceramic core blank after the powder cleaning is placed in a mullite crucible, placed in a high-temperature box furnace for high-temperature sintering, heated to 1200°C at a heating rate of 10°C / min and kept warm for 1h, then heated to 1500°C at a heating rate of 2°C / min and kept warm for 2h, then cooled to 1200°C at a cooling rate of 2°C / min, and cooled to room temperature at a cooling rate of 10°C / min to obtain the yttrium oxide ceramic core.
[0057] Example 2
[0058] This embodiment is an additive manufacturing method for an yttria ceramic core, and the specific process thereof includes the following steps:
[0059] Step 1, surface coating the spherical yttrium oxide powder: add granulated spherical yttrium oxide powder with a particle size of 10 μm into a ball mill, add 2 g of di(dioctyl pyrophosphate)vinyl titanate as a surface coating agent for every 100 g of spherical yttrium oxide powder, and use xylene as an organic solvent; add alumina ball milling beads of the same mass as the powder as abrasives, and the diameters of the added ball milling beads are 10 mm, 5 mm, and 2 mm in a ratio of 1:1:1; the horizontal rotation speed of high-energy ball milling mixing is 800 r / min, and the high-energy ball milling mixing time is 8 hours.
[0060] Step 2, performing surface activation treatment on the spherical yttrium oxide powder treated in step 1: adding a nonionic surfactant to the spherical yttrium oxide powder treated in step 1, adding 2g of fatty alcohol polyoxyethylene ether as a surfactant for every 100g of spherical yttrium oxide powder; continuing high-energy ball milling, the horizontal rotation speed of high-energy ball milling mixing is 400r / min, and the high-energy ball milling mixing time is 12h.
[0061] Step 3, cleaning, drying and crushing the spherical yttrium oxide powder treated in step 2: placing the spherical yttrium oxide powder treated by surface activation in step 2 into an alcohol solution with a volume percentage of 75% for ultrasonic cleaning for 15 minutes, with an ultrasonic frequency of 100kHz, and drying the spherical yttrium oxide after cleaning at a temperature of 90°C for 3 hours; crushing the dried spherical yttrium oxide powder with a pulverizer at a crushing speed of 1000r / min and a crushing time of 15s, and finally sieving the powder through a 1000-mesh sieve.
[0062] Step 4, mixing the spherical powder treated in step 3 with the irregular yttrium oxide powder according to particle size grading: ball-milling the modified spherical yttrium oxide powder with a particle size of 10 μm and the irregular yttrium oxide powder with a particle size of 30 μm in a mass ratio of 2.5:7.5, and adding ball milling beads with a diameter of 10 mm and 5 mm in a ratio of 1:1; the horizontal speed of the ball milling is 200 r / min, the vertical speed is 30 r / min, and the ball milling time is 5 h.
[0063] Step 5, the powder mixed in step 4 is subjected to binder jet printing: the required yttrium oxide ceramic core pattern is drawn by 3D modeling software, and printed by a binder jet device; the specific printing parameters are as follows: the printing layer thickness is 100 μm, the printing binder saturation is 67%, the printing number is 2 passes, the roller rotates counterclockwise, and the rotation speed is 60 r / min.
[0064] Step 6, solidify the yttrium oxide powder bed printed in step 5: put the printed powder bed into an oven, set the temperature to 120°C, and keep it warm for 3 hours to fully solidify the binder to form a firm yttrium oxide ceramic core blank.
[0065] Step 7, performing a powder cleaning treatment on the yttrium oxide ceramic core after the solidification treatment in step 6: removing excess yttrium oxide powder from the surface and the inside of the solidified yttrium oxide ceramic preform by brushing.
[0066] Step 8, high-temperature sintering the yttrium oxide ceramic core after powder cleaning in step 7 to obtain the yttrium oxide ceramic core: the yttrium oxide ceramic core blank after powder cleaning is placed in a mullite crucible, placed in a high-temperature box furnace for high-temperature sintering, heated to 1200°C at a heating rate of 10°C / min and kept warm for 1h, then heated to 1600°C at a heating rate of 2°C / min and kept warm for 2h, then cooled to 1200°C at a cooling rate of 2°C / min, and cooled to room temperature at a cooling rate of 10°C / min to obtain the yttrium oxide ceramic core.
[0067] Example 3
[0068] This embodiment is an additive manufacturing method for an yttria ceramic core, and the specific process thereof includes the following steps:
[0069] Step 1, surface coating the spherical yttrium oxide powder: add granulated spherical yttrium oxide powder with a particle size of 10 μm into a ball mill, add 3 g of di(dioctyl pyrophosphate)vinyl titanate as a surface coating agent for every 100 g of spherical yttrium oxide powder, and use xylene as an organic solvent; add alumina ball milling beads of the same mass as the powder as abrasives, and the diameters of the ball milling beads added are 10 mm, 5 mm, and 2 mm in a ratio of 1:1:1; the horizontal rotation speed of high-energy ball milling mixing is 800 r / min, and the high-energy ball milling mixing time is 12 h.
[0070] Step 2, performing surface activation treatment on the spherical yttrium oxide powder treated in step 1: adding a nonionic surfactant to the spherical yttrium oxide powder treated in step 1, adding 3g of fatty alcohol polyoxyethylene ether as a surfactant for every 100g of spherical yttrium oxide powder; continuing high-energy ball milling, the horizontal rotation speed of high-energy ball milling mixing is 400r / min, and the high-energy ball milling mixing time is 16h.
[0071] Step 3, cleaning, drying and crushing the spherical yttrium oxide powder treated in step 2: placing the spherical yttrium oxide powder treated by surface activation in step 2 into an alcohol solution with a volume percentage of 75% for ultrasonic cleaning for 20 minutes, with an ultrasonic frequency of 100kHz, and drying the spherical yttrium oxide after cleaning at a temperature of 100°C for 4 hours; crushing the dried spherical yttrium oxide powder with a pulverizer at a crushing speed of 1500r / min and a crushing time of 20s, and finally sieving the powder through a 1000-mesh sieve.
[0072] Step 4, mixing the spherical powder treated in step 3 with the irregular yttrium oxide powder according to particle size grading: ball-milling the modified spherical yttrium oxide powder with a particle size of 10 μm and the irregular yttrium oxide powder with a particle size of 30 μm in a mass ratio of 4:6, and adding ball milling beads with a diameter of 10 mm and 5 mm in a ratio of 1:1; the horizontal speed of the ball milling is 200 r / min, the vertical speed is 30 r / min, and the ball milling time is 6 hours.
[0073] Step 5, the powder mixed in step 4 is subjected to binder jet printing: the required yttrium oxide ceramic core pattern is drawn by 3D modeling software, and printed by a binder jet device; the specific printing parameters are as follows: the printing layer thickness is 120 μm, the printing binder saturation is 80%, the printing number is 2 passes, the roller rotates counterclockwise, and the rotation speed is 60 r / min.
[0074] Step 6, solidify the yttrium oxide powder bed printed in step 5: put the printed powder bed into an oven, set the temperature to 130°C, and keep it warm for 4 hours to fully solidify the binder to form a firm yttrium oxide ceramic core blank.
[0075] Step 7, performing a powder cleaning treatment on the yttrium oxide ceramic core after the solidification treatment in step 6: removing excess yttrium oxide powder from the surface and the inside of the solidified yttrium oxide ceramic preform by brushing.
[0076] Step 8, high-temperature sintering the yttrium oxide ceramic core after the powder cleaning in step 7 to obtain the yttrium oxide ceramic core: the yttrium oxide ceramic core blank after the powder cleaning is placed in a mullite crucible, placed in a high-temperature box furnace for high-temperature sintering, heated to 1200°C at a heating rate of 10°C / min and kept warm for 1h, then heated to 1700°C at a heating rate of 2°C / min and kept warm for 2h, then cooled to 1200°C at a cooling rate of 2°C / min, and cooled to room temperature at a cooling rate of 10°C / min to obtain the yttrium oxide ceramic core.
[0077] Example 4
[0078] The wettability of the granulated spherical yttrium oxide powder with the aqueous binder and the microstructure and performance of the yttrium oxide ceramic core samples prepared in different embodiments of the present invention are analyzed.
[0079] (1) Testing the wetting between granulated spherical yttrium oxide powder and aqueous binder before and after modification using a contact angle meter
[0080] From the microstructure diagram of granulated spherical yttrium oxide, it can be seen that the granulated spherical yttrium oxide powder is sintered together by even finer nano-yttrium oxide powder, and there are obvious gaps between the nano-yttrium oxide. Figure 1It can be seen that when the water-based binder is dripped on the granulated spherical yttrium oxide powder before modification, the binder is completely absorbed by the powder. When the water-based binder is dripped on the granulated spherical yttrium oxide powder after modification, the water-based binder forms a wetting angle of 42.6° on the yttrium oxide powder, indicating that the modified granulated spherical yttrium oxide powder does not absorb the water-based binder and has good wettability with it.
[0081] (2) Test the density and porosity of the sample by the Archimedes drainage method
[0082] It can be seen that the density and porosity of the yttrium oxide ceramic green samples printed by different mass ratios of 10 μm granulated spherical yttrium oxide powder and 30 μm irregular yttrium oxide powder are different (e.g. Figure 2 (shown in Figure 1), the granulated spherical yttria powder with a smaller particle size can fill the larger gaps between irregular powders; when the content of granulated spherical yttria powder is low, there are still some gaps between irregular powders that are not filled; when the content of granulated spherical yttria powder is high, the filling of irregular powders is affected, and the density of the powder bed will also decrease, resulting in an increase in the porosity of the green sample and a decrease in the density. The proportion of different particle sizes can be freely adjusted according to different needs, so as to achieve the preparation of yttria ceramics with different porosities.
[0083] (3) Test the bending strength of the specimen by three-point bending
[0084] like Figure 3 It can be seen that with the increase of sintering temperature, the flexural strength of yttrium oxide ceramic samples also increases. This is because with the increase of sintering temperature, the granulated spherical yttrium oxide powder can no longer exist in a spherical state, but is dispersed in nano form and filled in the irregular yttrium oxide voids, promoting the formation of sintering necks and improving the sintering strength.
[0085] Example 5: Test of wetting binder of granulated yttrium oxide powder before and after modification
[0086] Figure 5 The granulated yttrium oxide powder is wetted with the binder before and after modification. Figure 5 a is the particle before modification, from which it can be seen that the powder particles are completely filled with binder without any gaps. Figure 5 b is the modified particle, from which we can see that there is no obvious gap after the surface treatment, and the inside does not absorb the binder. Therefore, the binder exists between the modified yttrium oxide powder particles, which can form parts well.
[0087] Example 6
[0088] Di(dioctyl pyrophosphate) vinyl titanate (GR-311W) can be used to coat granulated spherical yttrium oxide powder. The purpose of the coating is to prevent the aqueous binder from entering the particles during the printing process, forming a protective film. Yttrium oxide itself will be hydrated when in contact with water to generate yttrium hydroxide. The pH changes of spherical yttrium oxide powders coated with di(dioctyl pyrophosphate) vinyl titanate at different contents in 40°C warm water are used to detect the coating effect of di(dioctyl pyrophosphate) vinyl titanate. Figure 6 As shown in the figure, the hydration speed of the uncoated yttrium oxide powder in water is relatively fast, and the pH is stabilized at about 9.47 after 140 minutes. As the amount of di(dioctyl pyrophosphate)ethylene titanate added continues to increase, the hydration speed of the yttrium oxide powder in water becomes slower and slower, and the degree of hydration also becomes slower and slower. When the amount of di(dioctyl pyrophosphate)ethylene titanate added increases to 4wt%, the pH of the aqueous solution stabilizes at about 7.02, and the yttrium oxide powder is basically not hydrated. Di(dioctyl pyrophosphate)ethylene titanate has a good coating effect on spherical yttrium oxide powder. Because di(dioctyl pyrophosphate)ethylene titanate is a chelated titanate coupling agent, it can chelate with the hydroxyl group or other active functional groups on the surface of yttrium oxide (such as the -OH group on the oxide surface). In addition, the chelate formed by the titanate forms a stable chemical film on the surface of yttrium oxide. This film is stable and not easy to react with water, which further prevents the entry of water-based binders.
[0089] Example 7
[0090] After coating with di(dioctyl pyrophosphate) vinyl titanate (GR-311W), the binder was effectively prevented from being absorbed by the spherical yttrium oxide powder, but the wettability between the water-based binder and the yttrium oxide powder was greatly reduced. The coated yttrium oxide powder was further activated with fatty alcohol polyoxyethylene ether. The activation effect of fatty alcohol polyoxyethylene ether on yttrium oxide powder was detected by measuring the wettability between the water-based binder and the yttrium oxide powder. Figure 7 As shown, the wettability of the yttrium oxide powder without activation treatment and the aqueous binder is poor, with a wetting angle of 92.5°. As the amount of fatty alcohol polyoxyethylene ether added continues to increase, the wettability of the yttrium oxide powder and the aqueous binder has been significantly improved. A wetting angle of less than 45° usually indicates that the liquid has very good wettability to the powder surface. In binder jet printing, a smaller wetting angle helps to enhance the adhesion between the binder and the material, ensuring better bonding performance. Fatty alcohol polyoxyethylene ether molecules contain both hydrophilic groups (ethylene oxide) and hydrophobic groups (hydrocarbon groups). The presence of these hydrophilic and hydrophobic groups enables the molecules to form a directional arrangement in the aqueous adhesive and the yttrium oxide surface, that is, the hydrophobic group faces the yttrium oxide powder surface GR-311W waterproof membrane, and the hydrophilic group faces the aqueous binder.
[0091] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
Claims
1. An additive manufacturing method for an yttria ceramic core, characterized in that: The following steps are involved: Step 1, performing surface coating treatment on spherical yttrium oxide powder; Step 2, performing surface activation treatment on the spherical yttrium oxide powder treated in step 1; Step 3, washing, drying and crushing the spherical yttrium oxide powder processed in step 2; Step 4, mixing the spherical powder processed in step 3 with the irregular yttrium oxide powder according to particle size grading; Step 5, performing bonding spray printing and molding on the powder mixed in step 4; Step 6, curing the yttrium oxide powder bed printed in step 5; Step 7, performing a powder removal treatment on the yttrium oxide ceramic core after the curing treatment in step 6; Step 8, high-temperature sintering the yttrium oxide ceramic core after the powder cleaning in step 7 to obtain the yttrium oxide ceramic core.
2. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 1, the surface coating treatment of the yttrium oxide powder is specifically performed as follows: granulated spherical yttrium oxide powder with a particle size of 10 μm is added to a ball mill, 1 to 3 g of di(dioctyl pyrophosphate) vinyl titanate is added to every 100 g of spherical yttrium oxide powder as a surface coating agent, and xylene is used as an organic solvent; alumina ball milling beads of the same mass as the powder are added as abrasives, and the diameters of the added ball milling beads are 10 mm, 5 mm, and 2 mm in a ratio of 1:1:1; the horizontal rotation speed of high-energy ball milling mixing is 800 r / min, and the high-energy ball milling mixing time is 4 to 12 h.
3. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 2, the yttrium oxide powder treated in step 1 is subjected to surface activation treatment as follows: a nonionic surfactant is added to the spherical yttrium oxide powder after treatment in step 1, and 1 to 3 g of fatty alcohol polyoxyethylene ether is added as a surfactant for every 100 g of spherical yttrium oxide powder; high-energy ball milling is continued, the horizontal rotation speed of the high-energy ball milling mixing is 400 r / min, and the high-energy ball milling mixing time is 8 to 16 h.
4. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 3, the spherical yttrium oxide powder treated in step 2 is cleaned, dried and crushed as follows: the spherical yttrium oxide powder treated in step 2 is placed in an alcohol solution with a volume percentage of 75% for ultrasonic cleaning for 10 to 20 minutes, the ultrasonic frequency is 100kHz, the spherical yttrium oxide is dried at a temperature of 80 to 100°C and a drying time of 2 to 4 hours after cleaning; the dried spherical yttrium oxide powder is crushed by a crusher at a crushing speed of 500 to 1500 r / min and a crushing time of 10 to 20 seconds, and finally the powder is sieved through a 1000-mesh screen.
5. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 4, the spherical powder treated in step 3 is mixed with irregular yttrium oxide powder by particle size grading as follows: the modified spherical yttrium oxide powder with a particle size of 10 μm and the irregular yttrium oxide powder with a particle size of 30 μm are ball-milled in different mass ratios of 1 to 4:9 to 6, and ball milling beads with diameters of 10 mm and 5 mm are added in a ratio of 1:1; the horizontal speed of the ball milling is 200 r / min, the vertical speed is 30 r / min, and the ball milling time is 4 to 6 h.
6. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 5, the powder mixed in the step 4 is subjected to binder jet 3D printing molding, specifically, the required yttrium oxide ceramic core pattern is drawn by 3D modeling software, and printing is performed by a binder jet device; the specific printing parameters are a printing layer thickness of 80 to 120 μm, a printing binder saturation of 54 to 80%, a printing number of 2 passes, a roller rotating counterclockwise, and a rotation speed of 60 r / min.
7. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 6, the yttrium oxide powder bed printed in the step 5 is cured by placing the printed powder bed in an oven, setting the temperature to 110-130° C. and keeping the temperature for 2-4 hours, so that the binder is fully cured to form a firm yttrium oxide ceramic core blank.
8. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: The process of performing powder cleaning on the yttrium oxide ceramic core after the solidification treatment in step 6 in step 7 is to remove excess yttrium oxide powder from the surface and the inside of the solidified yttrium oxide ceramic preform by brushing.
9. The additive manufacturing method of an yttria ceramic core according to claim 1, characterized in that: In the step 8, the yttrium oxide ceramic core after the powder cleaning in step 7 is subjected to high-temperature sintering. Specifically, the yttrium oxide ceramic core blank after the powder cleaning is placed in a mullite crucible, placed in a high-temperature box furnace for high-temperature sintering, heated to 1200°C at a heating rate of 10°C / min and kept warm for 1h, then heated to 1500°C / 1600°C / 1700°C at a heating rate of 2°C / min and kept warm for 2h, then cooled to 1200°C at a cooling rate of 2°C / min, and cooled to room temperature at a cooling rate of 10°C / min to obtain the yttrium oxide ceramic core.
10. The additive manufacturing method of an yttria ceramic core according to any one of claims 1 to 9, characterized in that: The porosity of the yttria ceramic core is 42.3-54.2%; and the bending strength is 12.2-28.3 MPa.
Citation Information
Patent Citations
High solid phase content ceramic slurry for photo-curing 3D printing and preparation process of ceramic slurry
CN107129283A
Photocuring 3D printing yttrium oxide ceramic core and preparation method thereof
CN113105240A
Binder for additive manufacturing of ceramic parts and bonding method
CN115074034A
3D printing zirconia composite ceramic slurry as well as preparation method and application thereof
CN118908726A
Surface treatment method of titanium powder and titanium powder produced by the method
KR102389504B1